Strategic Environmental Assessment Law in Kenya: Lacunae and Consensus - Okoth-Yogo, D. K. (Africa Environmental Review Journal, 2015)
Strategic Environmental Assessment [SEA] is a methodical process for examining the significance of decisions taken to ensure that environmental considerations and alternatives are addressed on parity with economic and social factors in policies, plans and programs [PPP] for developments. SEA counteracts some of the limitations of Environmental Impact Assessments [EIA] as they provide room for assessment of actions that transcends specific projects. EIAs, though firmly rooted in Kenya, take place after many strategic decisions have been made regarding specific projects. This paper not only discusses SEAs wholesomeness but also legal lacuna that negates its benefits as one of the tools for implementing environmental law objectives. It recommends that for SEA to be effective, it should either be explicit, or the definition and the provision of EIA expanded to include assessment of not only projects but also plans, policies and programs from universally spatial and sector-wide perspectives.